Grenzüberschreitungen und Grenzauflösungen in literarischen Darstellungen der Wirtschaftswelt - Jolanta Pacyniak (Recherches Germaniques)
In this article we analyse the problem of blurring and pushing the boundaries from an economic perspective. Our considerations are based on three novels from the years 1991, 2003 and 2012 by Uwe Timm, Burkhard Spinnen and Nora Bossong, all of which address some economic issues. The examined boundary problem manifests itself in the dissolution of the boundary between the concepts: work and leisure or idleness. Another reference point is the literary game that takes place between the fictional and autobiographical elements on the one hand, and the appearance and reality in economic affairs on the other. We can observe an increase in the chaotic and boundary-blurring elements in the description of economic problems in the analysed works.